Modernization of the Public Budget between the challenges of Financial Sustainability and fluctuations in Oil revenues Standard Analytical Study 1992-2020 - hacene benmoussa; morad djebara (Journal of Excellence for Economics and Management Research, 2022)
The study aims to analyze and evaluate the financial sustainability of the general budget and the challenges it faces in light of the successive financial and oil crises, and the extent of the state's ability to sustain funding sources using the VECM error correction model during the period between 1992-2020. It affected financial sustainability due to the association of public revenues with oil taxation and its impact on oil shocks, and that the financial situation in Algeria is not characterized by financial sustainability in light of the current circumstances and dependence on oil taxation, and therefore work to embody the modernization project on the ground, which was approved by the government starting from the year 2023 became necessary , by activating the Organic Law 15/18, and managing the budget according to the logic of results.